1999
DOI: 10.4141/a98-065
|View full text |Cite
|
Sign up to set email alerts
|

A simple, on-line processing method for improving beef tenderness

Abstract: A simple, on-line processing method for improving beef tenderness. Can. J. Anim. Sci. 79: 27-34. Traditional beef carcass suspension by the Achilles tendon allows considerable rigor shortening and decreased tenderness in some of the major muscles of the back and hindlimb. To reduce this effect, 60 market-weight (480 ± 42 kg) Hereford Angus cross cattle (30 steers and 30 heifers) of an estimated Canada 1 yield grade were used to compare the effects on meat quality of an on-line altered suspension (OLAS) under C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
18
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 17 publications
6
18
2
Order By: Relevance
“…Ultimate meat tenderness is highly dependent on the degree of alteration and weakening of myofibrillar structures, resulting in an increase in tenderness in aged compared with unaged meat (Koohmaraie and Geesink, 2006). Moreover, several authors have reported changes in both instrumental and sensory texture of beef from pelvic suspended compared with Achilles-suspended carcasses (Eikelenboom et al, 1998;Aalhus et al, 1999;Ahnströ m et al, 2009). Therefore, as indicated by our results, the greatest variation in shear force values is due to post-mortem changes.…”
Section: Proximate Analysissupporting
confidence: 61%
See 2 more Smart Citations
“…Ultimate meat tenderness is highly dependent on the degree of alteration and weakening of myofibrillar structures, resulting in an increase in tenderness in aged compared with unaged meat (Koohmaraie and Geesink, 2006). Moreover, several authors have reported changes in both instrumental and sensory texture of beef from pelvic suspended compared with Achilles-suspended carcasses (Eikelenboom et al, 1998;Aalhus et al, 1999;Ahnströ m et al, 2009). Therefore, as indicated by our results, the greatest variation in shear force values is due to post-mortem changes.…”
Section: Proximate Analysissupporting
confidence: 61%
“…Meat quality analyses Sarcomere length was measured as described by Aalhus et al (1999). Briefly, 2 g of muscle freed of fat and connective tissues were removed, scissor-minced and mixed in 20 ml of a 0.02 M ethylene glycol tetraacetic acid/0.25 M sucrose solution in a 50 ml centrifuge tube.…”
Section: Animal Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…After each carcass was split into sides (~30 min postmortem), the MOLAS treatment was applied to one side of the carcass, with alternation between the right and left sides of the carcass with alternate carcasses. MOLAS involved first severing the pelvic bone with a bone saw at the narrowest part of the body of the ilium (Aalhus et al 1999). That cut differed from the cut through the body of the ischium of the pelvic bone, described in publications by Marriott and Claus (1994) and Claus et al (1997).…”
Section: Preparation Of Carcass Sidesmentioning
confidence: 99%
“…Severing these tissues causes the longissimus thoracis et lumborum (LTL) to support more of the weight of the carcass side, reducing rigor related shortening in that muscle. Both the initial results of the Virginia researchers (Claus et al 1993;Wang et al 1994Wang et al , 1995 and results of a similar procedure tested at Lacombe (Aalhus et al 1999) indicated that pre-rigor cuts consistently increased sarcomere lengths and improved shear force and taste panel tenderness in muscles of the LTL. In the Lacombe study, shear force was reduced by as much as 2.5 kg (15-25%) and the proportion of unacceptable overall palatability scores was reduced from 20% in CON samples to 3% in treated samples.…”
mentioning
confidence: 97%